Fabrication and application of naturally sourced nano-pigments based on algal biomass in multifunctional coatings - Walaa M. Abd El-Gawad; Sayeda M. Abdo (Scientific Reports)
Abstract This work aims to synthesize economical and eco-friendly naturally sourced nano-pigments with bright colors, antimicrobial activity, and thermal stability from algal cells cultivated in wastewater, which are then harvested, dried, and converted into algal biomass (AB). Algal biomass (AB) was covered by a very thin nano-layer of either zinc ferrite or cerium ferrite, which does not exceed 10%. After the synthesis and characterization, these nanopigments were incorporated into alkyd resin in two proportions (2.5% and 5%). The antimicrobial activity and color of the produced coatings were investigated using the disc diffusion and CIELab methods, respectively. Besides, their thermal stability was examined using scanning electron microscopy (SEM) and thermal gravimetric analysis (TGA). The results of antimicrobial activity demonstrate that the effect of all coatings on fungi is greater than their effect on bacteria and that films containing 5% of nano-pigments gave an inhibition zone for microbes greater than those containing 2.5%. Additionally, the thermal stability results of the film containing algal biomass show very high weight loss, reaching 47.5% in group I and 76% in group II. While coatings containing zinc ferrite/AB and cerium ferrite/AB, weight loss doesn’t exceed 20%, and films containing 5% are the best.